Nivelación propuesta por la SENESCYT: Vivencias en la Universidad Central del Ecuador - Ortiz Herrera, Jorge Daniel (2017)
In the superior education a critical and permanent problem exists, which corresponds to the admission in the superior studies of the high schools formed by the half education. The Central University of the Ecuador has formulated different answers in the last decades, however the SENESCYT has imposed a model created from the theoretical discussion and this has been obligatory from 2013. The investigation looked for to verify its contribution to the solution of the problem and to compare with the previous immediate admission and a proposal outlined in 2016, the verification is carried out in existent three Faculties of eighteen; for that the yield was analyzed in mathematics and language, as well as the adaptation in the level of superior education. The results evidence that they cannot be generalized among the studied Faculties, the proposal of SENESCYT causes improvements in Careers with free entrance, but not in the other cases and is discovered that it is necessary a new proposal.